2015
DOI: 10.1371/journal.pone.0142563
|View full text |Cite
|
Sign up to set email alerts
|

Improving Multi-Epitope Long Peptide Vaccine Potency by Using a Strategy that Enhances CD4+ T Help in BALB/c Mice

Abstract: Peptide-based vaccines are attractive approaches for cancer immunotherapy; but the success of these vaccines in clinical trials have been limited. Our goal is to improve immune responses and anti-tumor effects against a synthetic, multi-epitope, long peptide from rat Her2/neu (rHer2/neu) using the help of CD4+ T cells and appropriate adjuvant in a mouse tumor model. Female BALB/c mice were vaccinated with P5+435 multi-epitope long peptide that presents epitopes for cytotoxic T lymphocytes (CTL) in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 48 publications
2
85
0
1
Order By: Relevance
“…For tumor induction, 1 × 10 6 CT26 tumor cells were inoculated subcutaneously into the right flank of anesthetized mice as described [18]. Tumor volumes (mm 3 ) were calculated with formula length × width × height × 0.52 that measured by a digital caliper.…”
Section: Tumor Challengementioning
confidence: 99%
“…For tumor induction, 1 × 10 6 CT26 tumor cells were inoculated subcutaneously into the right flank of anesthetized mice as described [18]. Tumor volumes (mm 3 ) were calculated with formula length × width × height × 0.52 that measured by a digital caliper.…”
Section: Tumor Challengementioning
confidence: 99%
“…Recall epitope assay indicated that 4 of the 5 epitopes successfully activated T cells and challenge assay results showed early activation of T H cells, elevated interferon and interleukin expression, and prolonged survival rates in vaccinated mice (202). Other studies have observed similar, positive results when employing this approach to targeting T cell activation (203)(204)(205)(206).…”
Section: Targeting Tcr Via Recombinant and Conjugate Approachesmentioning
confidence: 79%
“…Suitable linkers and adjuvants were used to combine top finalized epitopes from each protein that led to develop a multi epitope vaccine molecules ( Supplementary Table 6). As PADRE sequence was usually recommended to lessen the polymorphism of HLA molecules in the population (Ghaffari-Nazari et al, 2015), it was also considered to construct the final vaccine molecule. Here, adjuvants would enhance the immunogenicity of the vaccine constructs and appropriate separation of epitopes in the host environment would be ensured by the linker (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%